2012
DOI: 10.2174/1874387001206010008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation, Protein Composition and Potential Influences on Tendon Properties in Humans

Abstract: Sequence variations in genes that code for proteins involved in homeostatic processes within tendons may influence tendon mechanical properties. Since variants of the four genes COL5A1, TNC, MMP3 and GDF5 have been implicated in the aetiopathogenesis of tendinopathies, which is ultimately characterised by abnormal structural and regulatory processes, sequence variations in these four genes may also influence how the tendon functions mechanically, even in the absence of tendinopathy. For example, two reports of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 183 publications
(231 reference statements)
1
8
0
Order By: Relevance
“…revealed that the G allele of lys45Glu and the 6A allele of (–1171) 5A/6A variants associate with the highest level of circulating MMP‐3 in patients with rheumatoid arthritis. The results of the present study also agree with those of Foster et al . suggesting that the G variant of Lys45Glu SNP may promote elevated levels of MMP‐3 expression via increased MMP‐3 activation as a result of an altered interaction with other amino acids in the propeptide region.…”
Section: Discussionsupporting
confidence: 92%
“…revealed that the G allele of lys45Glu and the 6A allele of (–1171) 5A/6A variants associate with the highest level of circulating MMP‐3 in patients with rheumatoid arthritis. The results of the present study also agree with those of Foster et al . suggesting that the G variant of Lys45Glu SNP may promote elevated levels of MMP‐3 expression via increased MMP‐3 activation as a result of an altered interaction with other amino acids in the propeptide region.…”
Section: Discussionsupporting
confidence: 92%
“…In an earlier study we found that the GG genotype was a risk factor for Achilles tendinopathy but not Achilles tendon rupture in South Africans Caucasians ( Raleigh et al, 2009 ). The G allele of the rs679620 locus is known to increase MMP3 expression ( Foster et al, 2012 ), as it is in high linkage disequilibrium (LD) with the 5A allele of the rs3025058 variant ( Chen et al, 2012 ). The 5A allele has been reported to up-regulate MMP3 mRNA levels ( Ye, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are many non-genetic factors infl uencing fascial tissues. Many of these are primarily conditioned by genetic predispositions anyway (Foster, 2012). The determination of genetic factors is a complex problem whose analysis was not the aim of this study.…”
Section: Discussionmentioning
confidence: 99%